Pengaruh Citra Merek, Persepsi Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Di Hotel Maven Fatmawati Jakarta - Ayuska Anatasya; Verry Cyasmoro (Universitas Katolik Widya Karya Malang, 2023)
In the hospitality industry, the choices made by consumers when making purchases are of utmost importance for the survival of a company, particularly for Hotel Maven Fatmawati Jakarta, as they directly impact its profitability. This study aims to investigate the impact of brand image (X1), price perception (X2), and service quality (X3) as predictor variables on the decisions made regarding accommodations (Y) at Hotel Maven Fatmawati Jakarta. The research design utilized for this study is quantitative and based on surveys, employing an accidental sampling method with a sample size of 100 individuals who have previously made purchases at Hotel Maven Fatmawati Jakarta. The collected data was analyzed using multiple regression analysis, and primary data was directly obtained from the respondents. The research findings indicate that the independent variables collectively influence decisions regarding accommodations at Hotel Maven Fatmawati Jakarta. However, when examined individually, brand image and price perception do not significantly impact these decisions. On the other hand, service quality has a significant influence on accommodation decisions at Hotel Maven Fatmawati Jakarta.